Relationship between knowledge, attitudes and hygiene practices in food handlers in kiosks of Public Educational Institutions of Ate, 2017 - García Loyaga, Geordy Holmes (2019)
Objective: This research aims to determine the relationship among knowledge, attitude and practiceabout hygiene in food handlers who work in stalls of Public Schools in Ate, Methodology: This studyis a qualitative approach of transversal cut, of non-experimental design and correlacional type. Thepartipants were formed by the 145 food handlers of the 70 different stalls that are in the schools in Ate.the instrument used was a quiestionnaire about hygiene knowledge and attitude from the food handlersand a practice verification form. Results: The results showed that 78.6% of participants presented ahigh level in hygiene knowledge, and 87.6% presented a favorable level of hygiene attitude, while73% of the food handlers presented appropiate food hygiene practices. In respect with the correlationbetween hygiene knowledge and attitude of food handlers, using the test of Spearman Rho, it wasdemonstrated that statistically, there is a significant correlation (p<;05) between them. In addition,it was evidenced that there is a statistical significant correlation between hygiene knowledge andpractice from food handlers (p<;05); it is also observed that there is no statistically significant correlationbetween the attitude of food handlers and their practices (p>.05). Conclusions: In conclusion, foodhandlers have knowledge, attitude and appropriate practices on food hygiene, in most of the areas thatwere requested.